10 Things You Need to Know Before You Get Married - Victor W. Harris; Ginny Hinton (EDIS, 2012)
Americans love romantic books and movies that involve wedding vows and “happily-ever-after” endings. But in response to the high rates of divorce, a growing trend has emerged that focuses on developing a healthy marriage, rather than just the act of marriage. This 5-page fact sheet presents ten ways to achieve a healthy marriage of your own. Written by Victor W. Harris and Ginny Hinton, and published by the UF Department of Family, Youth and Community Sciences, August 2012.